(untitled) (World Bulletin of Public Health, 2023)
Currently, HIV infection remains one of the leading problems of global public health. Clinical signs of HIV infection are extremely diverse and are associated with many, including rheumatic, diseases. This review examines the problem of damage to the bone and joint system in HIV infection. The detailed clinical characteristics of individual nosological forms (HIV-associated arthritis, reactive arthritis, psoriatic arthritis, etc.) are presented, the issues of their differential diagnosis are considered. Modern approaches to the treatment of inflammatory joint diseases in HIV infection, including genetically engineered biological drugs, are analyzed.